Validation of neuropsychological personality scanning in a clinical sample of patients with mixed anxiety-depression disorder - Llaja Rojas, Victoria (2014)
The objective of this research is to determine the validity and reliability of neuropsychological Scanning Personality (SNP). in patients’ clinical sample with Mixed Disorder Anxiety - Depression before diagnosed throuhh of the Test of Zung and to establish the correlation and concurrent validity with the NEOPIR (Eysenk revised).The instrument used is the Scale: Scanning neurospicológico of the Personality,original version, based on the theoretical model informacional (Ortiz, 1994, 1997, 2004, 2004b)For the analysis of the information there were in use the SPSS Version 18, coefficient Cronbach’s Alpha, Construct validity by correlation item-test for temperament, intellect and Character , Pearson correlation, and concurrent validity with the revised Test Eysenk (NEOPIR). We found that the Scale SNP has content and construct validity of, demonstrating indices of validity and reliability of 0.9 in Total Scale in what in terms of its internal consistency, For temperament of 0.7 , 0.8 for intellect , and 0.7 for the character in the measurement of the structural components of the personality of our patients. Likewise in the qualitative analysis we have that the clinical findings of the patients with F41.2 correlate with the descriptive typologies and characteristics in Scanning of the three components structural of the personality.